1999
DOI: 10.1029/1999gb900006
|View full text |Cite
|
Sign up to set email alerts
|

Wintertime CO2 efflux from Arctic soils: Implications for annual carbon budgets

Abstract: Abstract. Estimates of annual carbon loss from arctic tundra ecosystems are based nearly entirely on measurements taken during the growing season in part because of methodological limitations but also reflecting the assumption that respiration during winter is near zero. Measurements of CO2 flux during winter, however, indicate significant amounts of carbon loss from tundra ecosystems throughout the 240-day nongrowing season. In our study during the 1996 and 1997 nongrowing seasons, winter carbon losses ranged… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
119
3

Year Published

2012
2012
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 179 publications
(137 citation statements)
references
References 30 publications
15
119
3
Order By: Relevance
“…CO 2 flux measurements reported in this study were generally in the upper range of winter emissions reported in the literature Skinner, 2007;Sommerfeld et al, 1996;Filippa et al, 2009;Liptzin et al, 2009;Rogiers et al, 2008;Brooks et al, 1997;Fahnestock et al, 1999). Whereas our results showed a clear seasonal pattern with (i) gradual decreases at the beginning of the snow-covered period, (ii) a mid-winter minimum, and (iii) increases in CO 2 flux during snowmelt, studies undertaken in the Rocky Mountains showed completely opposite behavior of steadily increasing CO 2 fluxes with progressing winter (Sommerfeld et al, 1996, Monson et al, 2006a.…”
Section: Seasonal Ghg Fluxescontrasting
confidence: 53%
See 1 more Smart Citation
“…CO 2 flux measurements reported in this study were generally in the upper range of winter emissions reported in the literature Skinner, 2007;Sommerfeld et al, 1996;Filippa et al, 2009;Liptzin et al, 2009;Rogiers et al, 2008;Brooks et al, 1997;Fahnestock et al, 1999). Whereas our results showed a clear seasonal pattern with (i) gradual decreases at the beginning of the snow-covered period, (ii) a mid-winter minimum, and (iii) increases in CO 2 flux during snowmelt, studies undertaken in the Rocky Mountains showed completely opposite behavior of steadily increasing CO 2 fluxes with progressing winter (Sommerfeld et al, 1996, Monson et al, 2006a.…”
Section: Seasonal Ghg Fluxescontrasting
confidence: 53%
“…There is also only one single study that explicitly measured the spatial variability of soil CO 2 effluxes for different ecosystem types during winter in Arctic Alaska . Case studies showed that soil CO 2 efflux ranged between 0.7 and 770 g CO 2 -C m −2 during the long snow-covered season, which corresponded to 10 to 40 % of the annual effluxes in arctic and subalpine ecosystems (Winston et al, 1997;Clein and Schimel, 1995;Melloh and Crill, 1996;Nykanen et al, 1995;Aurela et al, 2002;Fahnestock et al, 1999;Björkman et al, 2010b).…”
Section: Introductionmentioning
confidence: 99%
“…R e outside the growing season contributed 21.5 % in short-term grazing exclusion and 6.8 % in longterm grazing exclusion to the annual respiration emissions, which were similar to a sub-alpine grassland at Rigi Seebodenalpin (23.3 %) (Merbold et al, 2012). In addition, the CO 2 flux (2.1-16.8 mg m −2 h −1 ) outside the growing season from the alpine grassland in our study was comparable with previous studies in arctic tundra (2.5-7.5 mg m −2 h −1 ) (Fahnestock et al, 1999;Bubier et al, 2002), in temperate semiarid steppe (3.3-9.6 mg m −2 h −1 ) (Chen et al, 2013), and in sagebrush steppe (7.5-15.0 mg m −2 h −1 ) (Gilmanov et al, 2004). However, soil CO 2 emissions during the growing season (483.4-504.2 mg m −2 h −1 ) were lower than in subalpine grassland (610.0-810.0 mg m −2 h −1 ) (Rich et al, 2013).…”
Section: Effects Of Grazing Exclusion On Co 2 Fluxsupporting
confidence: 88%
“…Wintertime C losses can account to a significant part of the annual C budget (Fahnestock et al 1999), and the C efflux is likely to increase if the snow depth increases (Welker et al 2000;Larsen et al 2007a). In the mesic heath, cold-season (October-May) respiration accounted for 22 % of the annual respiratory CO 2 release, and rather surprisingly, photosynthetic activity outside the growing season accounted for 19 % of the annual gross CO 2 uptake, partly compensating for the respiratory C losses (Larsen et al 2007b).…”
Section: Exchange Of Greenhouse Gases In Subarctic Heath Ecosystemsmentioning
confidence: 99%